Konjunkturcykler i Danmark og Europa - Niels Arne Dam (Danmarks Nationalbank, 2008)
– Several countries at the core of the Euro area have experienced coincident business cycles during the most recent decades, while the Danish economy seemed detached from these cycles during the 1980's and part of the 1990's. To a large degree, the decoupling of the Danish economy reflects fundamental changes in the Danish economic policy during this period. Towards the end of the 1990's a remarkable business-cycle convergence occurred between most of the industrialised countries, as documented in a series of empirical analyses. In the same period, the correlation between Danish and Euro area business cycles increased markedly. Over the most recent years, however, this global convergence has decreased again, while the correlation between Euro-area core economies has remained high. The Danish economy has also maintained a relatively high business-cycle correlation with the Euro-area core countries.
Keywords: 330; Konjunktur; Konjunkturzusammenhang; Clusteranalyse; Dänemark; Eurozone; EU-Staaten